The hunt for computerized support in information security policy management: A literature review. (23rd January 2020) - Rostami, Elham; Karlsson, Fredrik; Kolkowska, Ella
Abstract : Purpose: The purpose of this paper is to survey existing information security policy (ISP) management research to scrutinise the extent to which manual and computerised support has been suggested, and the way in which the suggested support has been brought about. Design/methodology/approach: The results are based on a literature review of ISP management research published between 1990 and 2017. Findings: Existing research has focused mostly on manual support for managing ISPs. Very few papers have considered computerised support. The entire complexity of the ISP management process has received little attention. Existing research has not focused much on the interaction between the different ISP management phases. Few research methods have been used extensively and intervention-oriented research is rare. Research limitations/implications: Future research should to a larger extent address the interaction between the ISP management phases, apply more intervention research to develop computerised support for ISP management, investigate to what extent computerised support can enhance integration of ISP management phases and reduce the complexity of such a management process. Practical implications: The limited focus on computerised support for ISP management affects the kind of advice and artefacts the research community can offer to practitioners. Originality/value: Today, there are no literature reviews on to what extent computerised support the ISP management process. Findings on how the complexity of ISP management has been addressed and the research methods used extend beyond the existing knowledge base, allowing for a critical discussion of existing research and future research needs.